Implementasi Program Keluarga Harapan (PKH) Di Desa Tanjangrono Kecamatan Ngoro Kabupaten Mojokerto - Pratiwi Widiya Ningrum; Hendra Sukmana (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2022)
The Family Hope Program is a social assistance program for poor families as an effort to reduce poverty, improve the quality of human resources, as well as change behavior patterns that do not support improving the welfare of poor families. The implementation of the PKH program has not gone well because there are several indicators that cause the program not to run smoothly. This study aims to explain the Implementation of the Family Hope Program (PKH) in Tanjangrono Village, Ngoro District, Mojokerto Regency. This research method is descriptive qualitative. The type of data used in this study is secondary data based on periodic data in the form of data or instructions obtained from time to time where the data provides an overview of the progress of ongoing activities or circumstances. this research. Using online and offline data sources, including books, scientific papers, and some trusted news. This study shows the implementation of the Family Hope Program (PKH) in Tanjangrono Village is assessed from 4 indicators, namely communication, resources, disposition, and bureaucratic structure. In implementing PKH, the lack of coordination and communication between the village government and PKH employees or implementers in providing socialization to residents regarding the Family Hope Program (PKH), as well as human resources in Tanjangrono Village are still not competent in carrying out their responsibilities in carrying out their duties which can lead to the Family Hope Program. (PKH) has not run optimally as well as the lack of commitment from the village government and employees in carrying out the existing programs in Tanjangrono Village. On the other hand, the existence of an SOP to provide order in providing services to the community will also have a good impact on the local government of Mojokerto Regency because in Mojokerto Regency it is reduced.